1998
DOI: 10.5558/tfc74241-2
|View full text |Cite
|
Sign up to set email alerts
|

Selection of vertebrate wildlife indicators for monitoring sustainable forest management in Ontario

Abstract: Part of a recently advocated method of sustainable forestUne partie d'une methode recemrnent recommandee touchant development employs indicator species as h e filters to assess changes le developpernent durable des for& emploie les espkes indicatrices within ecosystems and landscapes. We used a series of criteria based en tant que filtres specifiques pour evaluer les modifications on biology, sampling methods, and legal or particular status to select survenant dans les ecosystemes et les paysages. Nous avons v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 9 publications
0
52
0
2
Order By: Relevance
“…Prairie and cerulean warblers, however, are associated with wooded areas, and they may be reasonable indicators of early and later successional forests, respectively. Neither of these warbler species, however, were identified by broader-scale experts (McLaren et al 1998), likely because both are at the northern edge of their breeding range (Robbins et al 1966). More southerly populations (in the United States) seem to be doing fine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prairie and cerulean warblers, however, are associated with wooded areas, and they may be reasonable indicators of early and later successional forests, respectively. Neither of these warbler species, however, were identified by broader-scale experts (McLaren et al 1998), likely because both are at the northern edge of their breeding range (Robbins et al 1966). More southerly populations (in the United States) seem to be doing fine.…”
Section: Discussionmentioning
confidence: 99%
“…More southerly populations (in the United States) seem to be doing fine. Although McLaren et al (1998) justified their choices and reasons for not including VTEs in their final list, most of the vertebrate wildlife indicators they suggested are relatively common and are unlikely to be good indicators. For instance, their masked shrew (an indicator of polewood mixedwood stands) is more correctly called the common shrew because it is so ubiquitous .…”
Section: Discussionmentioning
confidence: 99%
“…Zimmerman et al (2011) recommend that songbird monitoring studies continue beyond the expected turnover time (i.e., the life expectancy of the resident population of songbirds at the time the treatment was applied) of the study populations. McLaren et al (1998) suggested a list of possible wildlife indicator species for monitoring the effects of forest management in boreal Ontario. These included the masked shrew (Sores cinereus Kerr), rock vole (Microtus chrotorrhinus Mill.…”
Section: Are Songbirds and Small Mammals Affected By Vegetation Managmentioning
confidence: 99%
“…In Ontario, a list of indicator species to be used in the evaluation of forest operations has been developed (McLaren et al 1998). Although the formulation of criteria for selecting species is clear, rigorous and leads to an exhaustive list of indicators for Ontario's forests ecosystems, the operational feasibility of setting monitoring programs for each indicator at the scale of an FMU can be questioned.…”
Section: Planning and Environmental Indicatorsmentioning
confidence: 99%